PROFILE OF NUTRITIONAL STATUS, HEMOGLOBIN, LEUKOCYTES, PLATELET, HEMATOCRIT, ALBUMIN AND SEROLOGY TEST IN CHILDREN INFECTED WITH DENGUE VIRUS AT DR SOETOMO HOSPITAL YEAR 2015 - Zuhra, Zakirah (Stem Cell Research and Development Center, Universitas Airlangga, 2023)
The Dengue Virus Infection (DVI) triggers changes in the host's hematological, biochemical, and immunological aspects, affecting variables like hemoglobin (Hb), leukocytes (WBC), platelets (Plt), hematocrit (Hct), albumin (Alb), IgM, IgG, and NS1Ag Dengue. This study aims to investigate the demographic and clinical characteristics of DVI patients, considering factors such as gender, age, nutritional status, Hb, WBC, Plt, Hct, Alb, dengue serologic tests, and DVI stage. Using a cross-sectional descriptive approach, medical records of 74 subjects were analyzed. Subjects were categorized as DF (33.78%), DHF I (27.03%), DHF II (4.05%), DHF III (25.68%), and DHF IV (9.46%). Predominantly, subjects were aged 6-12 years (48.65%) and predominantly male (58.11%). Most patients had a normal nutritional status (50%), seen in both females and males (32.26%, 62.79%), with DF being dominant (14.86%, 28.92%). Over-nutrition occurred in DF, DHF without shock, and DHF with shock at rates of 12.5%, 33.33%, and 54.17%. DF prevailed in patients aged <6 years (17.57%), while DHF I, DHF II, DHF III were more common in those aged 6-12 years (14.86%, 2.70%, 16.22%), and DHF IV in those aged <6 years (8.11%). Key findings revealed increased Hb levels from DF to DHF, with 38 of 74 DVI patients exhibiting leukopenia. The DVI stage showed an inverse correlation with Plt levels. Hct levels rose in DHF patients, and they had relatively low Alb levels. Primary infections were more frequent in DF, while secondary infections were predominant in DHF with shock. The study also noted variations in over-nutrition prevalence across DVI stages among patients at Dr. Soetomo General Hospital Surabaya in 2015.